2020
DOI: 10.1186/s12909-020-02133-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of research productivity among physical therapy programs in the United States: an observational study

Abstract: Background: This study targeted the association of program characteristics of 203 Doctor of Physical Therapy (DPT) programs in the United States (US) reported by the Commission on Accreditation in Physical Therapy Education (CAPTE) in their 2017 Annual Accreditation Report (AAR) with measures of core faculty research volume. The association of institutional, program, and faculty characteristics of an institution with core faculty research volume was investigated. Methods: This observational study analyzed data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Studies have been conducted on the participation of undergraduate medical and dental students in research activities, and the related barriers are similar to those reported in this study, such as lack of knowledge [ 40 ], lack of time [ 41 ], and issues in the student-advisor relationship [ 42 ]. The literature covers various aspects related to scientific publication [ 11 , 43 , 44 ], but specific factors related to undergraduate thesis have received little attention. The most important factors related to publication seem to be having adequate facilities and receiving grants to conduct research [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have been conducted on the participation of undergraduate medical and dental students in research activities, and the related barriers are similar to those reported in this study, such as lack of knowledge [ 40 ], lack of time [ 41 ], and issues in the student-advisor relationship [ 42 ]. The literature covers various aspects related to scientific publication [ 11 , 43 , 44 ], but specific factors related to undergraduate thesis have received little attention. The most important factors related to publication seem to be having adequate facilities and receiving grants to conduct research [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The literature covers various aspects related to scientific publication [ 11 , 43 , 44 ], but specific factors related to undergraduate thesis have received little attention. The most important factors related to publication seem to be having adequate facilities and receiving grants to conduct research [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests that several factors affect a faculty member's ability to pursue research. [18][19][20][21][22] ese include faculty memberspecific characteristics such as the attainment of academic doctoral degrees 18 and having dedicated time to research or teaching 19 as well as institution-specific considerations such as institutional reliance on tuition revenues, 20,21 institutional control, 22 and research culture (as defined by Carnegie classification and research space). 22 However, the extent to which these factors influence the ability to engage in ER 15 specifically remains unknown.…”
Section: Review Of Literaturementioning
confidence: 99%